Potensi Daun Kelor (Moringa Oleifera) Sebagai Suplementasi Herbal Untuk Pencegahan Stunting; Literature Review - Susi Susilawati; Ruri Yuni Astari; Fitri Zakiah (Journal of Education Technology Information Social Sciences and Health, 2026)
Stunting is a chronic nutritional problem caused by malnutrition during the first 1000 days of life, impairing children's physical and cognitive growth. Moringa oleifera leaves are rich in protein, iron, calcium, and vitamins A and C, offering potential for stunting prevention. This study aimed to identify Moringa's bioactive compounds and analyze its potential as a herbal supplement to improve nutritional status in toddlers and pregnant women, using a literature review with a PRISMA-guided meta-aggregation approach. Searches of PubMed and Google Scholar yielded 25 eligible articles from 246 initial results. The synthesis showed 4 articles confirming bioactive compounds, while 21 articles demonstrated clinical effectiveness in improving toddlers' weight, height, and albumin levels, including benefits from supplementation during pregnancy. Program success at the community level was also shaped by product innovation and caregiver knowledge. Larger-scale clinical trials and dose-safety studies are needed before broad recommendation.